A new technology for the treatment of chromium electroplating wastewater based on biosorption. (June 2016) - Liu, Chang; Fiol, Nuria; Poch, Jordi; Villaescusa, Isabel
Graphical abstract: Highlights: New eco-technology for chromium electroplating wastewater treatment. Biosorption replaces traditional methods of Cr(VI) reduction in wastewater. Full process for metal elimination comprises biosorption followed by precipitation. Abstract: In this work, an electroplating wastewater treatment based on biosorption followed by flocculation/precipitation is proposed. Biosorption was carried out by using exhausted coffee which has proved to be an efficient low cost sorbent for metal ions and reducing agent of hexavalent chromium in our previous works. After biosorption Cr(VI) concentration in the effluent met the wastewater treatment plant discharge regulation limit for hexavalent chromium (0.5 mg L −1 ). The addition of a suitable concentration of coagulant/flocculant resulted in the precipitation of residual trivalent chromium and other metal ions. The high correlation coefficients between Cr(VI) and Cr(III) and conductivity and pH values measured during the biosorption process highlighted the possible use of these two parameters to monitor the process. Indeed, these two parameters measured online resulted to be effective indicators of both process development and the end point of the process. The merits of the proposed treatment which are considered over other techniques are much lower electrical energy consumption; less amount of chemicals addition and the possibility of chromium recovery from the sorbent at a quite high level of purity. Moreover, biosorption is an eco-friendly process and implies the reuse of a product at the end of its useful life rather than being disposed in landfill.